SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SISWA BERPRESTASI DI SMP NEGERI 1 POLOKARTO SUKOHARJO MENGGUNAKAN METODE WEIGHTED PRODUCT (WP) - Aqoid Mustofa Ardhi, Dwi Remawati , Sri Hariyati Fitriasih (STMIK Sinar Nusantara, 2017)
This research is to make decision support system from student selection achievement in SMP Negeri 1 Polokarto Sukoharjo which still done manually. The method used is weighted product. System design using UML. Testing this system aims to find the level of validity of the system that applies the weight of algorithm products with MS.excel calculation with the same criteria and the same weight on each alternative for the results of calculating the distance relative to the ideal solution manual. The result of this research is making decision support system from student achievement. Keywords: decision support system, student selection achievement, weighted product